2021
DOI: 10.1186/s12871-021-01283-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on intraoperative hemodynamics, recovery profile and postoperative pain in patients undergoing laparoscopic cholecystectomy: a randomized controlled trial

Abstract: Background To investigate the optimal dose of dexmedetomidine to maintain hemodynamic stability, prevent of cough and minimize postoperative pain for patients undergoing laparoscopic cholecystectomy. Methods One hundred twenty patients were randomly divided into D1, D2, D3 and NS groups, and dexmedetomidine 0.4, 0.6, 0.8μg/kg and normal saline were administrated respectively. Patients’ heart rate, systolic blood pressure and diastolic blood pressur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…Qin Ye et al, in a study of patients undergoing laparoscopic cholecystectomy, found that using the right dose of dexmedetomidine gives rise to hemodynamic stability [ 14 ]. At high doses, dexmedetomidine inhibits the release of epinephrine and norepinephrine by stimulating presynaptic a2-adrenoreceptors and increased parasympathetic tone, thereby promoting hemodynamic stability [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qin Ye et al, in a study of patients undergoing laparoscopic cholecystectomy, found that using the right dose of dexmedetomidine gives rise to hemodynamic stability [ 14 ]. At high doses, dexmedetomidine inhibits the release of epinephrine and norepinephrine by stimulating presynaptic a2-adrenoreceptors and increased parasympathetic tone, thereby promoting hemodynamic stability [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As studied by Qin Ye et al . [ 15 ] and Chilkoti et al .,[ 16 ] dexmedetomidine could effectively relieve pain in postoperative period as well as improve recovery profile as it reduces postoperative inflammatory markers and substance P released by surgical trauma. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved a total of 3841 studies. Among them, only 15 studies (980 patients) were included in the qualitative and quantitative analysis [4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Study Selection and Data Retrievalmentioning
confidence: 99%
“…Dexmedetomidine bolus used for tracheal intubation ranged from 1 mcg/Kg [4,17,19,21,22] to 0.01 mcg/Kg [15]. Five studies used a bolus dose higher than 0.7 mcg/Kg (137 patients to dexmedetomidine and 139 patients to placebo/no intervention) [4,17,19,21,22], five studies used a dose between 0.7 mcg/Kg and 0.4 mcg/Kg (177 patients to dexmedetomidine and 177 patients to placebo/no intervention) [ 13,14,20,24,26 ], four studies used a dose below 0.4 mcg/Kg (115 patients to dexmedetomidine and 115 patients to placebo/no intervention) [15,16,18 ,23 ] while one study [25] used both medium and high bolus dose of dexmedetomidine(90 patients to dexmedetomidine and 30 patients to placebo/no intervention).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation